Tragic failures : Alexandrian responses to tragedy and the tragic - Sistakou, Evina (Trends in classics. Supplementary volumes,, 2016)
This is the first study considering the reception of Greek tragedy and the transformation of the tragic idea in Hellenistic poetry. The focus is on third-century Alexandria, where the Ptolemies fostered tragedy as a theatrical form for public entertainment and as an official genre cultivated by the Pleiad, whereas the scholars of the Museum were commissioned to edit and comment on the classical tragic texts. More importantly, the notion of the tragic was adapted to the literary trends of the era. Released from the strict rules established by Aristotle about what makes a good tragedy, the major poets of the Alexandrian avant-garde struggled to transform the tragic idea and integrate it into non-dramatic genres. Tragic Failures traces the incorporation of the tragic idea in the poetry of Callimachus and Theocritus, in Apollonius' epic Argonautica, in the iambic Alexandra, in late Hellenistic poetry and in Parthenius' Erotika Pathemata. It offers a fascinating insight into the new conception of the tragic dilemmas in the context of Alexandrian aesthetics.